The dynamic structure of a flat small intestinal mucosa studied on the explanted rat jejunum. Issue 4 (April 1974) - Loehry, C. A.; Grace, R.
Abstract : Small pieces of jejunum with an intact blood supply were explanted to the anterior abdominal wall in rats. Six weeks after explantation the mucosa appeared totally flat in many areas, both histologically and under the dissecting microscope. The structure of the flattened mucosa was shown to be identical to that in coeliac disease with hypertrophied intervillous ridges. A dynamic study with tritium-labelled thymidine demonstrated a considerably increased turnover in the flat mucosa with some disorganization of cell production and migration.